Determinants of Physical Performance in People with Knee Osteoarthritis - Accettura, Angela J. (My University, 2012)
Osteoarthritis (OA) is a progressive degenerative joint disease affecting over 4 million Canadians. The knee is most commonly affected joint, making knee OA a leading cause of chronic disability. Leg power is more closely related to physical performance than leg strength in healthy older adults, but power has yet to be studied in people with knee OA. Self-efficacy beliefs, or the confidence one has in their own abilities, is a variable closely related to physical performance in people with knee OA.
The objective of this study was to identify the extent to which knee extensor strength, knee extensor power and self-efficacy explained variance in physical performance measures in adults with knee OA.
Thirty-three participants diagnosed with clinical knee OA were included (5 men; mean age 61.1 ± 6.2 y). Dependent variables included a timed stair ascent, a timed stair descent, and the six minute walk test (SMWT). Independent variables included self-efficacy beliefs for pain, mean peak knee extensor power and mean knee extensor strength.
Pearson correlations and linear regression models were completed using SPSS 15.
Average values on the numeric pain rating scale (NPRS), self-efficacy beliefs for pain and mean peak knee extensor power explained 34.7 % and 42.7% of the variance observed on the timed stair ascent and the timed stair descent, respectively. The determinants of the SMWT were different, with 29.4 % of the variance being explained by average NPRS and body mass index.
Similar to previous work conducted on healthy older adults, it appears that in adults with knee OA, knee extensor power is a closer determinant of physical performance when compared to knee extensor strength, on challenging everyday tasks, like ascending or descending a flight of stairs. For longer endurance type activities like the SMWT, the physical requirements may be different. Clinicians should consider these results when advising patients on the exercise interventions needed to maintain or improve physical performance.
Keywords: Knee; Osteoarthritis; Physical Performance; Medicine and Health Sciences; Rehabilitation and Therapy; Medicine and Health Sciences